Efectiveness Of Effective Cough In Expelling Sputum In Chronic Bronchitis Cases - Puguh Santoso; Sucipto, Sucipto (Jurnal EduHealth, 2024)
Chronic Bronchitis is a condition associated with excessive tracheobronchial mucus production, causing coughing that occurs for at least three months in one year for more than two consecutive years. The purpose of this study was to determine the Effectiveness of Effective Cough in Expelling Sputum in Chronic Bronchitis Cases at Kediri District Hospital. The research design in this study was descriptive. The location of this study was at the Lung Polyclinic of Kediri District Hospital. While the sample consisted of 6 respondents with a sampling technique, namely quota sampling. The measuring instrument used an observation sheet. The results of this study were that sputum discharge before being taught effective coughing was mostly (67%) able to come out, a small portion (33%) did not come out. Meanwhile, after being taught effective coughing, most (100%) can come out. So the conclusion is that the effectiveness of effective coughing in expelling sputum in cases of chronic bronchitis after being taught effective coughing techniques, most can come out. In addition, clients must breathe properly and do not need to cough hard to expel sputum.